In perspective of International Legal Protection Law, the Rohingya Refugee Crisis - Haryadi, Yukatari Fiorenza Ramada (Universitas Sebelas Maret, 2023)
The refugee issue is currently a serious challenge for the international community. Along with natural disasters or man-made crises, the problems faced by refugees are getting worse day by day. Currently, UNHCR still exists to provide refugee protection. A brief definition of refugees are people who have fled their native country due to persecution, conflict, public violence, or other conditions that have seriously upset public orders and need international protection. The Rohingya refugee crisis is one example of a situation that will be discussed. A quick overview of the Rohingya situation shows that they are Muslim inhabitants or ethnic groups whose presence is not acknowledged by the state. The Rohingya people were also the target of persecution, oppression, or assault, which drove many to leave their homeland in search of safety abroad. This article will clarify and evaluate how international law may defend or protect refugees from the Rohingya crisis.